2014
DOI: 10.1074/jbc.m113.539494
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Lipopolysaccharide in Escherichia coli Requires the Essential LapB Heat Shock Protein

Abstract: Background:The mechanism of coordination between LPS synthesis and translocation is unknown. Results: Two new proteins, LapA and LapB, co-purify with LPS transport proteins. lapB mutants display defects in lipid A and core assembly. Conclusion: lapB mutants accumulate precursor LPS core species and exhibit elevated levels of LpxC. Significance: Coordinated assembly of LPS is a critical step for targeting to the outer membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
270
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(284 citation statements)
references
References 67 publications
(110 reference statements)
13
270
1
Order By: Relevance
“…Previously, we showed that the balanced biosynthesis of LPS requires the essential LapB protein and in its absence transcription of the rpoE gene is significantly induced (9). ⌬lapB mutants synthesize excess LPS with a significant proportion of LPS comprised of precursor forms and also have a dysfunctional Lpt translocation system (9).…”
Section: Defects In the Lps Assembly Also Induce The Rpoep3 Promotermentioning
confidence: 99%
See 4 more Smart Citations
“…Previously, we showed that the balanced biosynthesis of LPS requires the essential LapB protein and in its absence transcription of the rpoE gene is significantly induced (9). ⌬lapB mutants synthesize excess LPS with a significant proportion of LPS comprised of precursor forms and also have a dysfunctional Lpt translocation system (9).…”
Section: Defects In the Lps Assembly Also Induce The Rpoep3 Promotermentioning
confidence: 99%
“…Thus, one might miss genes whose products require the expression of whole operons or regulatory sRNAs. To overcome such limitations, a previously described complete genomic library in a mediumcopy p15A vector (9,35) was introduced to identify clones that exhibit a Lac up or down phenotype. These multicopy approaches identified qseG and several genes encoding lipoproteins (csgG, pgaB, spr, yhdV, yceB, yddW, and yghB), which, when overexpressed, increase the rpoEP-lacZ activity (Tables 1 and 2).…”
Section: Tablementioning
confidence: 99%
See 3 more Smart Citations